PERSEPSI MAHASISWA AKUNTANSI TENTANG KEILMUAN AKUNTANSI DAN SOFT SKILL (BAHASA INGGRIS DAN TEKNOLOGI INFORMASI) TERHADAP KESIAPAN MENGHADAPI TANTANGAN ERA REVOLUSI INDUSTRI 4.0 - Sandila Elatul Latifah; Junaidi Junaidi; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2020)
The purpose of this research is to find out how the influence of accounting scientific variables, English soft skill variables and information technology soft skills variables on readiness in facing the challenges of the industrial revolution era 4.0. The sample in this study were 100 students from two universities in the city of Malang. The sampling used is purposive sampling method. This type of research is quantitative with primary data obtained directly from students majoring in accounting at Malang Islamic University and Maulana Malik Ibrahim State Islamic University of Malang and collecting data using a questionnaire using a Likert scale. The analytical tool used in this study is multiple linear regression analysis by of SPSS 2019. The results are accounting scientific, english language and information technology simultaneously have a positive and significant effect on readiness in facing challenges of the industrial revolution era 4.0. Partially, accounting scientific variables, english and information technology shows that a positive and significant effect on readiness in facing the challenges of the industrial revolution era 4.0.Keywords: Accounting Science, English Soft Skill, Information Technology Soft Skill and Readiness to Face the Challenges of the Industrial Revolution Era 4.0